Emerging future studies : a proposed methodology for future studies emerging from the BA scoping project. - Gannaway, Deanne; Trent, Faith; Upton, Hayley; Price, Sarah (Australian Learning and Teaching Council, 2008)
Report from a project that aimed: To understand the nature and role of a Bachelor of Arts degree in contemporary Australia; To map the diverse Bachelor of Arts programs on offer in Australia between 2001-2008; To identify the major strengths, difficulties, capabilities and contributions of the program; and to provide rich base-line data on the nature and models of BAs to be accessible for future curriculum planning for arts faculties. This report presents an outcome of the BA scoping project: the identification of areas requiring further investigation and the development of interventions to enhance the experience of Bachelor of Arts students.